2020
DOI: 10.1177/2309499019896871
|View full text |Cite
|
Sign up to set email alerts
|

The impact of posterior epidural adipose tissue on postoperative outcomes after posterior decompression surgery for lumbar spinal stenosis: A prospectively randomized non-inferiority trial

Abstract: Study design: The present study is a prospectively randomized study. Objective: The objective of the study was to evaluate the impact of posterior epidural adipose tissue (PAT) on postoperative outcome following lumbar decompression surgery for lumbar spinal stenosis (LSS) by whether PAT was removed or preserved during the surgical procedure. Summary of background data: In posterior decompression surgery for LSS, PAT is routinely removed without knowledge of its role and significance. However, considering adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although some studies have suggested the histopathological features of the EF, subsequent studies have rarely reported a better definition of its function. Spine physicians rarely pay attention to EF, and it is mostly linked to epidural fibrosis formation after spinal surgery [17][18][19][20][21][22][23][24][25][26] and clinically uncharacterized back pain [24,27,28]. Recently, novel studies with different views on EF have focused on its regenerative or immunomodulatory function, especially with respect to MSCs derived from EF.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested the histopathological features of the EF, subsequent studies have rarely reported a better definition of its function. Spine physicians rarely pay attention to EF, and it is mostly linked to epidural fibrosis formation after spinal surgery [17][18][19][20][21][22][23][24][25][26] and clinically uncharacterized back pain [24,27,28]. Recently, novel studies with different views on EF have focused on its regenerative or immunomodulatory function, especially with respect to MSCs derived from EF.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue has been shown to represent a rich source of MSCs, and studies have shown that EVs derived from human adipose tissue MSCs can be used to ameliorate tissue damage in various disease models [ 13 , 14 , 15 ]. Epidural fat tissue is inevitably exposed during spinal surgery and spontaneously diminishes after spinal surgery [ 23 ]. Recently, the need for research on the characteristics and functions of epidural fat tissue has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…It has been possible to extract EVs from epidural adipose-derived mesenchymal stem cells, and such EVs have been confirmed to exhibit anti-inflammatory effects in a spinal cord injury animal model [ 21 ]. The epidural fat surrounds the dura matter of the spinal cord or nerve root [ 22 , 23 ]. However, the role and function of epidural fat are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[ 59 ] Although epidural fat is often decreased in the stenotic area, [ 49 ] posterior decompression for treatment of lumbar spinal stenosis includes further removal of posterior epidural fat. [ 60 ] Kyphoscoliosis is a combination of both kyphosis and scoliosis (abnormal outward and lateral curvature of the spine, respectively). This condition leads to asymmetrical distribution of epidural fat within the concave portion of the spinal curvature, ultimately displacing the spinal canal and its contents in the opposite direction.…”
Section: Is Epidrual Fat Important?mentioning
confidence: 99%
“…[ 61 ] In another study, following lumbar decompression surgery for lumbar spinal stenosis, postoperative outcomes worsened (pain intensity and a deteriorated score on the Oswestry (low back) Disability Index) amongst the group whose posterior epidural fat was removed. [ 60 ]…”
Section: Is Epidrual Fat Important?mentioning
confidence: 99%